Incidental News Consumption On Social Media Among Gen Z: A Case Study Of The 'Immortal Basketball Club' Community In South Tangerang, Banten - Medo Maulianza; Nur Asni Gani; Ella Xenia Maharani (INJECT (Interdisciplinary Journal of Communication), 2025)
This qualitative study investigates the process of Incidental News Exposure on social media among Generation Z. Utilizing Sanda Erdelez's five-stage Information Encountering model, the research confirms that INE is a dominant mode of news consumption, largely superseding deliberate news seeking due to social media architecture. Key findings reveal that the process is highly systematic: The Noticing and Stopping stages are driven by sophisticated algorithmic curation, repetition, and affective factors like curiosity and boredom, often transforming passively encountered content into active engagement. Crucially, the Examining stage demonstrated that news utility is primarily defined by social currency, the ability to facilitate peer conversations before any pragmatic or civic value. While the exposure is incidental, it acts as a Catalyst for Deliberate Action, prompting users to verify and seek deeper, intentional information. However, highly engaging incidental content frequently displaces the user’s original intent, confirming INE's significant structural power in dictating information flow. The study concludes that news providers must adapt to Gen Z's reliance on selective incidental exposure by prioritizing casual presentation and social relevance to remain effective.